2015
DOI: 10.1001/jama.2015.13134
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms for Cancer Resistance in Elephants and Comparative Cellular Response to DNA Damage in Humans

Abstract: IMPORTANCE Evolutionary medicine may provide insights into human physiology and pathophysiology, including tumor biology. OBJECTIVE To identify mechanisms for cancer resistance in elephants and compare cellular response to DNA damage among elephants, healthy human controls, and cancer-prone patients with Li-Fraumeni syndrome (LFS). DESIGN, SETTING, AND PARTICIPANTS A comprehensive survey of necropsy data was performed across 36 mammalian species to validate cancer resistance in large and long-lived organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
510
6
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(560 citation statements)
references
References 38 publications
20
510
6
1
Order By: Relevance
“…The p53 response is activated in part through increased protein levels and decreased degradation when the p53/Mdm2/4 complex is disrupted; for example, in response to oncogene activation, nuclear stress, and DNA damage (Vousden and Lu 2002;Reinhardt and Schumacher 2012;Hock and Vousden 2014;Khoo et al 2014;Meek 2015). The significant role of p53 in response to DNA damage is highlighted by the recent discovery of multiple functional copies of the Tp53 gene in elephants (Abegglen et al 2015). The Tp63 gene also shows a response to DNA damage, acting as a major regulator of the response in female germ cells (Suh et al 2006;Gonfloni et al 2009;Levine et al 2011).…”
mentioning
confidence: 99%
“…The p53 response is activated in part through increased protein levels and decreased degradation when the p53/Mdm2/4 complex is disrupted; for example, in response to oncogene activation, nuclear stress, and DNA damage (Vousden and Lu 2002;Reinhardt and Schumacher 2012;Hock and Vousden 2014;Khoo et al 2014;Meek 2015). The significant role of p53 in response to DNA damage is highlighted by the recent discovery of multiple functional copies of the Tp53 gene in elephants (Abegglen et al 2015). The Tp63 gene also shows a response to DNA damage, acting as a major regulator of the response in female germ cells (Suh et al 2006;Gonfloni et al 2009;Levine et al 2011).…”
mentioning
confidence: 99%
“…A more recent example of a comparative genomics approach to identify anti-cancer mechanisms leveraged the genome of the African elephant to investigate the genomic basis of reduced tumorigenesis within this species [14]. The results of this comparative study identified approximately 20 duplications of the p53 tumor-suppressor gene in the African elephant genome, which likely contribute to a decreased rate of tumorigenesis in the elephant.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that elephant cells have 20 copies of the T P 53 gene as compared to the single copy observed in human cells. Elephant cells were also found to carry out p53-dependent apoptosis at a much higher rate than human cells for the same amount of DNA damage [29].To test the effect of increasing the number of copies of the T P 53 gene, we took the full vertebrate network Nv described above and increased the basal and kinase-dependent rates of production of p53, while keeping all other parameters constant. We found that this would cause the level of threshold T2, shown in Fig.…”
mentioning
confidence: 99%